Monitoring power-law creep using the failure forecast method - Corcoran,J; Davies,C (International Journal of Mechanical Sciences, 2018)
Creep is considered to be the life limiting damage mechanism in many load bearing high temperature components. A range of different parameters determine the creep life of a component, many of which are unlikely to be known to sufficient accuracy to enable satisfactory estimation of remnant life. Instead,the integrity of a component shouldbe established through direct measurement of the response of the component to the operating conditions. Creep deformation is shown to be a positive feedback mechanism; anincreasein strain leadsto an increasing strain rate. It has recently been shown that as a consequence of positive feedback the Failure Forecast Method, a generalised framework for predicting time to criticality based on rates of change of damage, may beapplied for remnant life calculations. A range of strain rate based assessments have been proposed in the literature but it is proposed that the Failure Forecast Method unifies many of these techniques and provides additional insight into creep behaviour by virtue of the underlying positive feedback. The methodology has been demonstrated using experiment datasets that are pertinent to creep in high temperature pressure vessels and piping; it is shown that failure times are accurately predicted shortly after the minimum creep strain rate.